2018
DOI: 10.3892/or.2018.6878
|View full text |Cite
|
Sign up to set email alerts
|

FOXN3 is downregulated in osteosarcoma and transcriptionally regulates SIRT6, and suppresses migration and invasion in osteosarcoma

Abstract: Forkhead box N3 (FOXN3) has been reported to be downregulated in numerous cancers, including laryngeal, oral squamous cell and hepatocellular carcinomas, and diffuse large B-cell lymphoma. FOXN3 was proposed to serve as a tumor suppressor; however, the function of FOXN3 in osteosarcoma (OS) remains unknown. The present study suggested that FOXN3 was notably downregulated in OS tissues compared with in adjacent normal tissues, and the expression of FOXN3 was negatively correlated with tumor size, metastasis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…28 In recent years, studies on FOXN3 have suggested that it may play dual roles in different tumours. Acting as a tumour suppressor gene, FOXN3 is reduced in several types of tumours, such as HCC, colon cancer and osteosarcoma, 9,10,19 but it is upregulated in ovarian cancer and breast cancer, where it acts as an oncogene. 11,29 One explanation for the diverse effects of FOXN3 may be due to the specific cellular and tissue environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 In recent years, studies on FOXN3 have suggested that it may play dual roles in different tumours. Acting as a tumour suppressor gene, FOXN3 is reduced in several types of tumours, such as HCC, colon cancer and osteosarcoma, 9,10,19 but it is upregulated in ovarian cancer and breast cancer, where it acts as an oncogene. 11,29 One explanation for the diverse effects of FOXN3 may be due to the specific cellular and tissue environment.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor forkhead box N3 (FOXN3), as a member of the forkhead box N superfamily, participates in several biological processes, including the cell cycle, cell differentiation, epithelial-mesenchymal transition, gene transcription and glucose metabolism. 9-13 Previous studies have shown that the downregulated expression of FOXN3 is observed in various malignancies, such as hepatocellular carcinoma (HCC), colon cancer, ERα-positive breast cancer, Hodgkin lymphoma, head and neck cancer, lung cancer, adult glioblastoma multiforme, T cell acute lymphoblastic leukaemia (ALL)and osteosarcoma, 9,10,12,[14][15][16][17][18][19] and the FOXN3 expression level is associated with the prognosis of some cancers. Abstract Introduction: The expression of forkhead box N3 (FOXN3), also known as checkpoint suppressor 1 (CHES1), is reduced in many types of tumours.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been limited studies on the roles of SIRT6 in osteosarcoma [32][33][34][35]. Furthermore, the role of SIRT6 in the progression of osteosarcoma has been reported controversially [32,33,35].…”
Section: Introductionmentioning
confidence: 99%
“…In osteosarcoma cells, the PARP inhibitor, olaparib, potentiates the therapeutic e cacy of doxorubicin [31]. However, there have been limited studies on the roles of SIRT6 in osteosarcoma [32][33][34][35]. Furthermore, the role of SIRT6 in the progression of osteosarcoma has been reported controversially [32,33,35].…”
mentioning
confidence: 99%